Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2008
DOI: 10.1063/1.2969407
|View full text |Cite
|
Sign up to set email alerts
|

Observation of superluminal and negative group velocities in a Mach–Zehnder interferometer

Abstract: We demonstrate superluminal and negative group velocity regimes in a linear passive Mach–Zehnder interferometer. This phenomenon occurs in a narrow frequency region around the interferometer’s transmission minima. Experiments are performed in the radio frequency range by using coaxial cables and 1×2 wave splitters. Group velocities of 2c and tunneling with a maximum fractional advancement of 0.12 were measured for electromagnetic sinusoidal wave packets of 2 μs width. These results agree with theoretical predi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
27
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 15 publications
0
27
0
Order By: Relevance
“…The superluminal motion does not contradict causality and no information can be transmitted with velocity larger than the velocity of light. Indeed, the effect has been observed in several experiments (see e.g., [8][9][10][11]).…”
Section: Introductionmentioning
confidence: 89%
“…The superluminal motion does not contradict causality and no information can be transmitted with velocity larger than the velocity of light. Indeed, the effect has been observed in several experiments (see e.g., [8][9][10][11]).…”
Section: Introductionmentioning
confidence: 89%
“…This led the authors to point out this structure as a good candidate for obtaining negative group velocity. Time domain experiments performed with Gaussian acoustic pulses [32] and sinusoidally modulated RF wave packets [33] corroborated these findings. By tuning the pulse carrier frequency slightly off the transmission minima, superluminal propagation was also detected [33].…”
Section: Introductionmentioning
confidence: 58%
“…This two-path interferometer has been shown to sustain fast-light propagation for frequencies close to the transmission minima [31][32][33]. In [31], frequency-domain characterization of an asymmetric loop structure (asymmetric MZI) built with coaxial cables showed negative phase jumps around the transmission minima.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…Unlike these systems, we recently demonstrated superluminal and negative group velocity regimes in a linear and passive Mach-Zehnder interferometer 13 (MZI). We showed that anomalous dispersion in a narrow frequency region around the interferometer's transmission minima is strong enough to hold these propagation regimes without the need of periodically microstructuring, doping, or using non-linear media in the interferometer's arms.…”
Section: Introductionmentioning
confidence: 98%